Existence and Multiplicity of Nontrivial Solutions for a Class of Semilinear Fractional Schrödinger Equations. (26th September 2017) - Du, Xinsheng; Mao, Anmin
Abstract : This paper is concerned with the existence of solutions to the following fractional Schrödinger type equations: - ∆ s u + V x u = f x, u,     x ∈ R N, where the primitive of the nonlinearity f is of superquadratic growth near infinity in u and the potential V is allowed to be sign-changing. By using variant Fountain theorems, a sufficient condition is obtained for the existence of infinitely many nontrivial high energy solutions.